Odpowiedź :
Odpowiedź:
[tex] \frac{ log_{2}(15) - 3.5( log_{2}(3) + log_{2}(5) )}{ log_{2}(45) - log_{2}(3) } = \frac{ log_{2}(15) - 3.5( log_{2}(3 \times 5)) }{ log_{2}(45 \div 3) } = \frac{ log_{2}(15 )- 3.5( log_{2}(15) ) }{ log_{2}(15) } = \frac{ log_{2}(15) (1 - 3.5)}{ log_{2}(15) } = - 2.5[/tex]
[tex]tex] \frac{5 log_{5}(18) - 4 log_{5}(2) - 9 log_{5}(3) } { log_{5}(18) - log_{5}(3) } = \frac{log_{5}( {18}^{5} \div {2}^{4} \div {3}^{9} )}{ log_{5}(18 \div 3) } = \frac{log_{5}( {2}^{5} \times {3}^{10} \div {2}^{4} \div {3}^{9} )}{ log_{5}(18 \div 3) } = \frac{ log_{5}(2 \times 3) }{ log_{5}(6) } = \frac{ log_{5}(6) }{ log_{5}(6) } = 1[/tex]